Saturday arvo, St. Kilda Pier, Melbourne, 1961 - Carter, Jeff, 1928-2010. (1961)
"To this day a weekend afternoon walk on the pier is a popular event. A fire in 2003 destroyed the famous kiosk, located a hundred or so metres out over the waters of Port Phillip Bay." -- Description supplied by photographer.
Title supplied by photographer.
Part of collection: Jeff Carter collection of photographs, 1952-2002.
Also available online
Keywords: Walking -- Victoria -- Melbourne -- Photographs; Families -- Victoria -- Melbourne -- Photographs; St. Kilda Pier (Vic.) -- Social life and customs -- Photographs